2013
DOI: 10.1017/s0007114513001876
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of β-conglycinin on renal function and nephrin expression in early streptozotocin-induced diabetic nephropathy rats

Abstract: The objective of the present study was to investigate the effects of b-conglycinin and soya isoflavones on diabetic nephropathy (DN). DN was induced by an intravenous injection of streptozotocin (25 mg/kg) in spontaneously hypertensive rats. DN rats were divided into a non-diabetic group (C, control group) and three DN groups (D, DN with control diet; B, DN þ control diet with one-eighth of casein replaced by b-conglycinin as the protein source; and I, DN þ control diet with 0·01 % soya isoflavones). After a 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…SP contains all of the essential amino acids and also offers a good balance among nonpolar amino acid, polar amino acid and charged amino acid. SP has been investigated as the food additives, water emulsions and nutraceutical encapsulation in the form of nanoparticles, microspheres and hydrogels 20-23. It was reported that the hydrolysate of SP had the ability to inhibit angiotensin I-converting enzyme (ACE) which could be used to treat hypertension 24 and the ACE inhibition peptides derived from SP could lower blood pressure of spontaneously hypertensive rats 25.…”
Section: Introductionmentioning
confidence: 99%
“…SP contains all of the essential amino acids and also offers a good balance among nonpolar amino acid, polar amino acid and charged amino acid. SP has been investigated as the food additives, water emulsions and nutraceutical encapsulation in the form of nanoparticles, microspheres and hydrogels 20-23. It was reported that the hydrolysate of SP had the ability to inhibit angiotensin I-converting enzyme (ACE) which could be used to treat hypertension 24 and the ACE inhibition peptides derived from SP could lower blood pressure of spontaneously hypertensive rats 25.…”
Section: Introductionmentioning
confidence: 99%
“…β‐conglycinin improved hyperglycaemia and kidney nephron expression in rats with STZ‐induced diabetes. [ 19 ] Soy protein hydrolysates demonstrated inhibitory activity against hypertension. [ 20 ] These data suggest that soy proteins including peptides protect renal glomeruli by inhibition of hyperglycaemia or hypertension in diabetic condition.…”
Section: Discussionmentioning
confidence: 99%
“…One scientist proposed that DN caused by type 1 and type 2 diabetes should be considered and treated separately because of diverse pathophysiology . Accumulating evidence indicates that a soybean supplement decreases albuminuria and glycemia in a murine model of insulin‐dependent diabetes . Nevertheless, the effect of dietary soy on an insulin‐independent model is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that soy β‐conglycinin increases glucose uptake in muscle by regulating the AMPK signaling pathway and decreases the blood glucose level in a rat model of STZ‐induced diabetes . Furthermore, β‐conglycinin maintains kidney protein expression in a mouse model of STZ‐induced diabetes . Genistein, a major soy isoflavone, has been reported to have an anti‐inflammatory effect in a model of insulin‐dependent diabetes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation